Kandungan Senyawa Bioaktif dan Aktivitas Biologis Ekstrak Daun Rhizophora apiculata Asal Perairan Teluk Awur, Jepara - Mirsa Septiana Mutik; Mada Triandala Sibero; Widianingsih Widianingsih; Subagiyo Subagiyo; Rudhi Pribadi; Dwi Haryanti; Ambariyanto Ambariyanto; Retno Murwani (Universitas Diponegoro, 2022)
Rhizophora apiculata is a type of mangrove that has the ability to adapt to extreme environmental conditions such as temperature, low oxygen levels, and high salinity. This adaptability affects the production of secondary metabolites. Information about the antibacterial activity of this mangrove against MDR (Multi-Drug Resistant) bacteria is still very limited. The content of secondary metabolites produced by mangrove R. apiculata is also expected to affect antioxidant activity against free radicals. The purposes of this study were to examine the presence of bioactive compounds by phytochemical tests and to evaluate the antibacterial activity against MDR bacteria such as Pseudomonas aeruginosa, Escherichia coli, Bacillus cereus, and Bacillus subtilis; and antioxidants property of R. Apiculata leaves that were collected from Teluk Awur, Jepara. The leaves were extracted using the multilevel maceration method with solvent sequence n-hexane, ethyl acetate and methanol. Metabolite finger printing using TLC method was carried out to detect the presence of alkaloids, flavonoids, saponins, phenolics, quinones, steroids, and triterpenoids. The antibacterial test was carried out using agar well diffusion method while the antioxidant test was carried out using the DPPH method. The results of the phytochemical test showed that there were groups of alkaloids and steroids in the n-hexane solvent; alkaloids, phenolics, and steroids in ethyl acetate solvent; as well as alkaloids, flavonoids, phenolics, and saponins in methanol solvents. The results of this study indicate that R. apiculata from Teluk Awur Coastal Waters, Jepara had no potential as an antibacterial against MDR (Multi-Drug Resistant) bacteria, however the methanol extract has the potential to be used as an antioxidant with an IC50 value of 85.999 ppm. The bioautography showed that compounds from the phenol group, flavonoids, triterpenoids and b-carotene pigments acted as antioxidant agents in the leaf extract of R. apiculata. Rhizophora apiculata merupakan salah satu jenis mangrove yang memiliki kemampuan beradaptasi terhadap kondisi lingkungan ekstrem seperti suhu, kadar oksigen rendah dan salinitas tinggi. Kemampuan beradaptasi tersebut mempengaruhi produksi matabolit sekunder. Informasi mengenai kemampuan aktivitas antibakteri mangrove jenis ini melawan bakteri MDR (Multi Drug Resistent) masih sangat terbatas. Kandungan metabolit sekunder yang dihasilkan mangrove R. apiculata ini juga diharapkan dapat mempengaruhi aktivitas antioksidan melawan radikal bebas. Tujuan dari penelitian ini adalah untuk mengkaji kandungan senyawa bioaktif serta aktivitas biologis berupa antibakteri melawan bakteri MDR Pseudomonas aeruginosa, Escherichia coli, Bacillus cereus dan Bacillus subtilis; dan antioksidan dari ekstrak daun mangrove R. apiculata asal perairan Teluk Awur, Jepara. Sampel diekstraksi menggunakan 3 pelarut berbeda (n-heksana, etil asetat dan metanol) dengan metode maserasi bertingkat. Analisis metabolit sidik jari dilakukan menggunakan plat KLT untuk mengetahui kandungan senyawa alkaloid, flavonoid, saponin, fenolik, kuinon, steroid dan triterpenoid. Uji antibakteri dilakukan menggunakan metode sumuran sedangkan uji antioksidan dilakukan menggunakan metode DPPH. Hasil uji fitokimia menunjukkan terdapat golongan senyawa alkaloid dan steroid pada pelarut n-heksana; alkaloid, fenolik dan steroid pada pelarut etil asetat; serta alkaloid, flavonoid, fenolik dan saponin pada pelarut metanol. Hasil penelitian ini mengindikasikan bahwa R. apiculata asal perairan Teluk Awur, Jepara tidak potensial sebagai antibakteri melawan bakteri MDR (Multi Drug Resistent), akan tetapi ekstrak metanol potensial digunakan sebagai antioksidan dengan nilai IC50 85,999 ppm. Tahapan bioautografi menunjukkan bahwa senyawa dari golongan fenol, flavonoid, triterpenoid dan pigmen b-karoten berperan sebagai agen antioksidan pada ekstrak daun R. apiculata.